Study on overburden failure characteristics and ground pressure behavior in shallow coal seam mining underneath the gully - Zhang, Jie; Wang, Li; Yang, Tao; Gao, Shoushi; He, Yifeng; Wu, Jianjun (Frontiers in Earth Science, 2024)
Introduction: This study focuses on investigating the characteristics of overburden failure and ground pressure behavior in shallow coal seam mining beneath a gully. The research is conducted at the 135201 working face of Shaliang Coal Mine in the Shenfu Mining Area. Methods: The study employs physical similarity simulation tests, theoretical analysis, and field measurements to analyze the ground pressure and overburden failure characteristics at the working face. Results: The research findings indicate that the ground pressure is stronger in the uphill section compared to the gully bottom and downhill sections. The weighting interval in the uphill section is the smallest. A mechanical analysis model for the failure structure of the key stratum in the uphill section is established based on monitored ground pressure data and physical simulation test results. A calculation formula for the weighting interval in the uphill section is derived. The relationship between the caving interval, the thickness of the key stratum in the uphill section, and the gully slope is also analyzed. The on-site measurements align well with the theoretical results. Discussion: The study proposes a prediction method for ground pressure and suggests hazard prevention and control measures for shallow coal seam mining beneath a gully based on the research findings.